Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1590/s1677-5538.ibju.2022.99.13
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant gonadotropin therapy to improve spermatogenesis in nonobstructive azoospermic patients – A proof of concept study

Abstract: Purpose: Nonobstructive azoospermia (NOA) associated with primary spermatogenic failure is a common cause of male infertility usually considered untreatable; however, some reports have suggested that hormonal stimulation to boost the intra-testicular testosterone level and spermatogenesis might increase the chance of achieving pregnancy using homologous sperm. Materials and Methods: We report a series of eight NOA males who received long-term treatment with recombinant human chorionic gonadotropin twice a week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Sperm harvested from the seminiferous tubules are cryopreserved for future use. Our preferred method for freezing testicular sperm is vitrification using 'The Cell Sleeper method' (9,27,28). Briefly, Cell Sleepers consist of an outer vial, an inner tray, and a screw cap.…”
Section: Our Clinical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm harvested from the seminiferous tubules are cryopreserved for future use. Our preferred method for freezing testicular sperm is vitrification using 'The Cell Sleeper method' (9,27,28). Briefly, Cell Sleepers consist of an outer vial, an inner tray, and a screw cap.…”
Section: Our Clinical Approachmentioning
confidence: 99%
“…For these reasons, we do not support the routine use of TESA for NOA males. However, TESA is still carried out, for example, in low resource centers, particularly in patients with a history of previous positive retrieval by TESA or a biopsy report showing hypospermatogenesis (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Combining hCG with FSH may be beneficial in these patients as hCG boosts intratesticular testosterone production. Some patients with nonobstructive azoospermia fitting this group have experienced improvements in sperm retrieval rates after hormonal treatment ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Laursen and colleagues from Denmark and Brazil performed in page 471 (5) a nice study about the recombinant gonadotropin therapy to improve spermatogenesis in nonobstructive azoospermic patients and concluded that hormonal therapy with recombinant gonadotropins could be considered in infertile men with nonobstructive azoospermy as an alternative to sperm donation. Large-scale studies are needed to substantiate hormone stimulation therapy with recombinant gonadotropins in routine clinical practice for this severe form of male infertility.…”
mentioning
confidence: 99%